1998
DOI: 10.1021/la971217i
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Chain Length and Mole Fraction Dependence of the Stability of Tetrakis(cumylphenoxy)phthalocyanine and Alcohol Langmuir Films

Abstract: While it has been known for about 10 years that octadecanol stabilizes Langmuir−Blodgett films of copper tetrakis(cumylphenoxy)phthalocyanine films, the mechanism for this stabilization is not fully understood. To understand more completely the molecular interactions responsible for making octadecanol a good transfer promoter, we studied mixed films' isotherms of tetrakis(cumylphenoxy)phthalocyanine and various saturated alcohols ranging in length from 13 to 24 carbons. By varying mole fraction and alcohol cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that incorporation of transfer promoters such as arachidic acid, stearyl alcohol, and stearamide can produce high quality LB multilayers of porphyrins or phthalocyanines. 16,17 Ohigashi et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that incorporation of transfer promoters such as arachidic acid, stearyl alcohol, and stearamide can produce high quality LB multilayers of porphyrins or phthalocyanines. 16,17 Ohigashi et al…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve phthalocyanine LB film quality, various transfer promoters, such as arachidic acid, stearyl alcohol and steramide, have been used with phthalocyanines. 16,17 Liu et al reported that the most critical factors determining the stability and quality of LB films formed using arachidic acid as a transfer promoter are the pH value of the subphase and the presence of divalent cations such as Cd 2+ and Ba 2+ . 18 The results show that the divalent cations interact with dissociated carboxylic groups of arachidic acids to form a "disoap", which apparently enhances the LB film stability.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the LB technique is most effective in controlling thickness and structure on a molecular level . Hence, the LB films of Pc derivatives substituted at the periphery of their structure with various bulky alkyl and/or alkoxy groups, including tert -butyl, 3a, 9b hexyl,3b octyl, decyl, 3b, dodecyl, methoxy, butoxy, , octyloxy, ,14b benzyloxyethoxy, decyloxy, or cumylphenoxy, 3b,,, have been prepared and characterized in detail because of their good amphiphilic character.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of 2-DCPP/AA, the transfer ratios are close to 1 (0.94 ± 0.17) up to 18 multilayer depositions, which indicates improvement in the deposition quality due to the presence of arachidic acid. It has been reported that incorporation of transfer promoters such as arachidic acid, stearyl alcohol, and stearamide can produce high-quality LB multilayers of porphyrins or phthalocyanines [8][9][10][11][12][13]. Ohigashi et al [25] proposed that the transfer promoter played a role as stiffening poles for the stack of phthalocyanines in LB multilayers.…”
Section: Resultsmentioning
confidence: 99%
“…However, difficulties in obtaining excellent quality for LB films of porphyrins have been found due to aggregation. Thus transfer promoters such as stearyl alcohol, stearamide, and arachidic acid (AA) have been incorporated with porphyrins or phthalocyanines to improve the quality of the LB films [8][9][10][11][12][13]. In addition, one may be able to control molecular aggregation and orientation in LB films by changing the mixing ratios of the transfer promoter and the porphyrin [9].…”
Section: Introductionmentioning
confidence: 99%